Answer: g = 2
================================================
Work Shown:
![a \bowtie b = a + \sqrt{b+\sqrt{b+√(b+...)}}\\\\7 \bowtie g = 7 + \sqrt{g+\sqrt{g+√(g+...)}} = 9\\\\\sqrt{g+\sqrt{g+√(g+...)}} = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/j8inbd8dxb7s40e4ijnl6ifeaf5aq50556.png)
After subtracting 7 from both sides.
Note how because we have an infinite sequence of nested radicals, we can let
which means x is equal to 2 as well.
This lets us say
![\sqrt{g+\sqrt{g+√(g+...)}} = √(g+x) = x](https://img.qammunity.org/2021/formulas/mathematics/high-school/8ba5iiimdk9mrk05pw8rtarfof7v95y3mu.png)
Solve the equation
for x to get
![√(g+x) = x\\\\g+x = x^2\\\\x^2-x-g = 0\\\\x = (-b\pm√(b^2-4ac))/(2a)\\\\x = (-(-1)\pm√((-1)^2-4(1)(-g)))/(2(1))\\\\x = (1\pm√(1+4g))/(2)\\\\x = (1+√(1+4g))/(2) \ \text{ or } \ x = (1-√(1+4g))/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/dth53qhfy5l15mnytu4a29m2rojskvgogd.png)
Since x is positive, this means we only focus on the first equation in the last line above.
Earlier we let x be equal to the infinite nested radicals involving g, but x is also equal to 2. So plug in x = 2 and use that to find g.
![x = (1+√(1+4g))/(2)\\\\2 = (1+√(1+4g))/(2)\\\\4 = 1+√(1+4g)\\\\3 = √(1+4g)\\\\9 = 1+4g\\\\1+4g = 9\\\\4g = 8\\\\g = 2\\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/6osb33nw0zbkaigg98b0i0yok58ldjankj.png)
As a check, we can do the following
![7 + \sqrt{2+√(2)} \approx 8.84775906502258\\\\7 + \sqrt{2+\sqrt{2+√(2)}} \approx 8.96157056080647\\\\7 + \sqrt{2+\sqrt{2+\sqrt{2+√(2)}}} \approx 8.9903694533444\\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/mq8oyg14gx87d8e7j5evup0yd3o8rm5ab3.png)
we're slowly approaching 9